2012
DOI: 10.14429/djlit.32.2.1598
|View full text |Cite
|
Sign up to set email alerts
|

Blogs on Marketing Library Services

Abstract: The paper identifies blogs in the area of marketing of library and information services and assesses their features and contents during January to June 2009. It is found that six blogs on marketing of library services are active and cover variety of features, frequency, file formats, web resource categories and subjects including marketing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Further research on the effectiveness of Web 2.0 application are done by [15] and [16] in which, they reported that marketing through Facebook group are among the top ranking in promoting online databases. [17] reported another application of the social media which is Blogs are also identified as an effective promotional tools. Web 2.0 is also identified be interrelated with Marketing 2.0 as web element is taken to the marketing concept.…”
Section: Promoting Library Servicesmentioning
confidence: 99%
“…Further research on the effectiveness of Web 2.0 application are done by [15] and [16] in which, they reported that marketing through Facebook group are among the top ranking in promoting online databases. [17] reported another application of the social media which is Blogs are also identified as an effective promotional tools. Web 2.0 is also identified be interrelated with Marketing 2.0 as web element is taken to the marketing concept.…”
Section: Promoting Library Servicesmentioning
confidence: 99%
“…Kaushik and Arora (2012) report on identifying blogs in the area of marketing library and information services. There are also reports on the involvement of students in marketing efforts.…”
Section: Background On Marketing and Promotional Efforts By Librariesmentioning
confidence: 99%